The relationship between benefit finding and fear of progression in patients with chronic heart failure: Mediating role of coping style and moderating role of hospitalization frequency - Meijia Gao; Jie Meng; Jianglin Fan; Yimiao Tian; Zhimin Feng; Shaoying Du (Journal of Health Psychology, 2026)
This cross-sectional study investigated the moderated mediating roles of coping style and hospitalization frequency in the benefit finding–fear of progression relationship among 332 heart failure patients. Findings suggested that resignation coping mediated the impact of benefit finding on fear of progression, implying that alleviating such resignation coping may improve patients’ fear of progression. Furthermore, hospitalization frequency emerged as a significant negative moderator of resignation coping’s mediating effect. Consequently, this suggests that interventions aimed at improving resignation coping may mitigate the detrimental effect of benefit finding on fear of progression, especially for those experiencing more frequent hospitalizations.